Ethical issues of monitoring sensor networks for energy efficiency in smart buildings: a case study. (October 2017) - Cascone, Ylenia; Ferrara, Maria; Giovannini, Luigi; Serale, Gianluca
Abstract: The development of Internet of Things (IoT) based sensors has become crucial for analyzing and optimizing the energy-performance of buildings. However, researchers and professionals should be prepared to deal with the social and thus ethical issues arising from the use of such technologies. Based on a real case-study, we present a detailed analysis of the networks of stakeholders and the consequent ethical issues related to the implementation of energy and IEQ sensors network in an Italian university campus. Alternative scenarios for eliminating or reducing the criticalities related to security and privacy issues are proposed.